A sero epidemiological study of SARS-CoV-2 among nursing and paramedical staff in government general hospital, Kurnool - M., Keerthana; S., Pushpalatha; S., ShanthiKumari; Savolu, Cynthia S.; A., Sreedevi (International Journal Of Community Medicine And Public Health, 2021)
Background: Nurses and paramedical staff face a high risk of infection due to excessive COVID-19 exposure. In this study, SARS-CoV-2 antibodies were measured among nurses and paramedical staff, with an aim to determine the seroprevalence of SARS-CoV-2 and the characteristics associated with it. Methods: After obtaining IEC Clearance and informed consent from the study subjects, a cross sectional study was conducted from August to September, 2020. Data was collected from 127 nurses and paramedical staff, Government general hospital, Kurnool, selected by simple random sampling, using a semi-structured questionnaire and chemiluminescence immunoassay test for which IgM antibodies cut off value was 10 AU/ml. Test results and participant characteristics were recorded and data was analysed by MS Excel 13. Results: Among the study participants, seroprevalence was found to be 2.4%. Majority were females (66.9%). Most of them were aged 20-29 (24.4%) followed by 40-49 (19.7%) and 50-59 (10.2%) years. 56.7% were working in COVID wards. 42.5% worked in 3-6 hour shifts. Conclusions: The present study did show a low prevalence of IgM among nurses and paramedical staff. This might be an indicator that the personal protection measures were effective. Further it can provide an overview of the current seroprevalence of the health care workers.